HUBUNGAN KANDIDIASIS INTERTRIGINOSA DAN DIABETES MELITUS TIPE 2 DI POLIKLINIK KULIT DAN KELAMIN RSUD DOKTER SOEDARSO PONTIANAK PADA TAHUN 2012 - ., Farhana Mardila (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background. Intertriginous candidiasis is a type of cutaneous candidiasiswhich is located at the axila, inguinal, intergluteal, inframammary,interdigitalis, glands penis, and umbilicus. One of the risk factors ofintertriginous candidiasis patient is people with diabetes mellitus (DM).The increase of glucose concentration makes more susceptible frominfection. Objective. Define the association between intertriginouscandidiasis and DM type 2. Method. This research was a case controlstudy which took place in Dermatovenereology Outpatient Clinic RSUD dr.Soedarso from June until November 2013. The minimum sample for thisresearch was 126 people and divided into two groups. The case groupconsisted of 63 people and the control group consisted of 63 people. Thesubjects were selected by using consecutive sampling and analyzed bychi-square test. Result. There was an association between intertriginouscandidiasis with DM type 2 (p= 0,01). Odds Ratio (OR) value of thisresearch was 2,621 (IK 95% : 1,246 5,516). Conclusion. Intertriginouscandidiasis is associated with DM type 2 and people with DM type 2 havea possibility of 2,621 times higher risk of acquiring intertriginouscandidiasis than people without diabetes mellitus.Keyword : Intertriginous Candidiasis, Diabetes Mellitus (DM) Type 2